Study on impact of six sigma in Malaysia Manufacturer electric and electronic companies - Norsyuhada, Taib (2008)
Six Sigma applications is a one of the effective Total Quality Management tools in order to improve productivity in industry. However, while many benefits of Six Sigma is increasingly reported in other country, it is not very common among local company because lack of disclosure and many companies afraid to take a high risk. Furthermore, although there have been numerous case studies, comprehensive discussions, books and websites addressing Six Sigma, a very little academic research has been done to examine the impact of the Six Sigma application in local industry. This project has been created to measure the impact on a profit side, improving productivity and the benefits to the companies that implementing Six Sigma application. Survey project were used as the main research instrument in this project. Test result based on sample of 36 different companies in Malaysia manufacturer electric and electronics industry revealed that the implementation succeed to achieve all the benefits and the impact in profit side.